2019
DOI: 10.21037/jtd.2019.07.37
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of air pollutants on daily mortality and hospitalizations due to cardiovascular and respiratory diseases

Abstract: is one of the districts in Chiang Mai, Thailand facing high level of seasonal air pollution every year, the exposure of community dwellers to outdoor air pollutants 24 hours a day during seasonal smog period because of their open-air housing style, and agricultural occupational hazard. In addition, Chiang Dao hospital is the only available hospital serving the community with open-air wards; therefore we could certainly to identify the association between air pollution and mortality of hospitalized patients. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 34 publications
4
71
0
6
Order By: Relevance
“…After adjusting for the remaining pollutants each time, the effects of CO were attenuated. Previous studies also reported unstable associations between ambient CO and COPD occurrences, hospitalizations, and emergency visits [32][33][34]. The effects of ambient CO on COPDrelated mortality require further con rmation in future research.…”
Section: Discussionmentioning
confidence: 82%
“…After adjusting for the remaining pollutants each time, the effects of CO were attenuated. Previous studies also reported unstable associations between ambient CO and COPD occurrences, hospitalizations, and emergency visits [32][33][34]. The effects of ambient CO on COPDrelated mortality require further con rmation in future research.…”
Section: Discussionmentioning
confidence: 82%
“…Analysis performed in 22 European cohorts within the multicentre European Study of Cohorts for Responsible Editor: Philippe Garrigues Air Pollution Effects (ESCAPE) revealed that long-term exposure to fine particulate air pollution is associated with naturalcause mortality, also when considering concentration ranges below European annual mean upper limits (Beelen et al 2014). It has been also demonstrated that deaths related to cardiovascular and respiratory system diseases, as well as cancers, remain in close relationship with air pollution (Beelen et al 2014;Pothirat et al 2019). Among the air pollutants, ambient particular matters play an important role, and so far, many studies have been completed assessing their impact on the incidence and pathogenesis of cardiovascular, respiratory and other deadly diseases that account for the largest percentage of deaths nowadays (Ye et al 2001;Araujo et al 2008;Madrigano et al 2011;Nemmar et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Results for ozone (O 3 ), PM smaller than 10 microns (PM10), carbon monoxide (CO), sulfur dioxide (SO 2 ), and nitrogen dioxide (NO 2 ), were inconsistent (12)(13)(14)(15)(16)(17). More specifically, O 3 levels had a positive relationship with heart failure (18), hospital admissions, global mortality (19), and respiratory and cardiovascular mortality (19,20). Eight studies investigated the association between OHCA and short-term exposure to O 3 levels (10)(11)(12)15,(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%